STUDIES ON THE CULTURAL ECOSYSTEM SERVICES IN MALACCA CITY - Rosehan, Nur Shazwanie; Abas, Azlan; Aiyub, Kadaruddin (PLANNING MALAYSIA, 2020)
The benefits from ecosystem services have the prospective and potential to improve the Malay urban design and increase the quality of life. However, rapid development and urbanization activities are increasingly causing a conversion from the original functions and changes that can affect the urban environment. This paper aims to update current understanding of the concept of Malay cultural ecosystem services in Malacca City. Quantitative research through the survey method to 150 Malay respondents have been carried out in order to identify the parameters describing the types and value of the Malay cultural ecosystem services in the city context. The result revealed aesthetic value, recreational, tourism, social relations, spiritual and educational as the most significance parameters of the Malay cultural ecosystem services. The paper concluded that only through good practices from all parties can reduce the incredible development effects as political, economic and social systems is inevitable and constantly generates new demand.